Morphologic vascular anomalies detected during migraine surgery. Issue 11 (November 2022) - Raposio, Edoardo; Raposio, Giorgio; Del Duchetto, Denise; Tagliatti, Erica; Cortese, Katia
Abstract: Although there is increasing evidence of migraine headaches having extracranial origins, the exact mechanisms underlying the pathogenesis of surgically treated migraines continue to be poorly investigated and described. We studied the microscopic and ultrastructural characteristics of superficial temporal artery (STA) and occipital (OA) artery in the auriculotemporal and great occipital trigger points of migraine patients to determine their possible role in migraine etiopathogenesis. Fifteen biopsies, 10 of STA and 5 from OAs, were collected intraoperatively during migraine surgery and immediately processed for optical and ultramicroscopic analysis. We detected the following anomalies in all the specimens: (a) endothelial damage with internal elastic lamina fragmentation and intimal thickening; (b) marked irregularity in the shape and metachromasia of the vascular smooth muscle cells (VSMCs), separation of cells by abundant extracellular matrix and vacuoles. The electron microscopy analysis confirmed that presumed VSMCs infiltrated the intima layer revealing a consistent shift of VSMCs from contractile to synthetically active phenotypes, endosome-like organelles, multilamellar structures, abundant extracellular vacuoles filled with fine granular material and membranes, and extracellular vesicles in the matrix space surrounding synthetically active cells. Our study revealed specific alterations in the vasculature at the neurovascular bundles of the temporal and occipital trigger sites. These findings are indicative of an active involvement of the arteries in the auriculotemporal and great occipital trigger sites in evoking migraine.